Effects of isometric resistance training on resting blood pressure: individual participant data meta-analysis. Issue 10 (October 2019) - Smart, Neil A.; Way, Damien; Carlson, Debra; Millar, Philip; McGowan, Cheri; Swaine, Ian; Baross, Anthony; Howden, Reuben; Ritti-Dias, Raphael; Wiles, Jim; Cornelissen, Véronique; Gordon, Ben; et al.
Abstract : Background: Previous meta-analyses based on aggregate group-level data report antihypertensive effects of isometric resistance training (IRT). However, individual participant data meta-analyses provide more robust effect size estimates and permit examination of demographic and clinical variables on IRT effectiveness. Methods: We conducted a systematic search and individual participant data (IPD) analysis, using both a one-step and two-step approach, of controlled trials investigating at least 3 weeks of IRT on resting systolic, diastolic and mean arterial blood pressure. Results: Anonymized individual participant data were provided from 12 studies (14 intervention group comparisons) involving 326 participants (52.7% medicated for hypertension); 191 assigned to IRT and 135 controls, 25.2% of participants had diagnosed coronary artery disease. IRT intensity varied (8–30% MVC) and training duration ranged from 3 to 12 weeks. The IPD (one-step) meta-analysis showed a significant treatment effect for the exercise group participants experiencing a reduction in resting SBP of −6.22 mmHg (95% CI −7.75 to −4.68; P  < 0.00001); DBP of −2.78 mmHg (95% CI −3.92 to −1.65; P  = 0.002); and mean arterial blood pressure (MAP) of −4.12 mmHg (95% CI −5.39 to −2.85; P  < 0.00001). The two-step approach yielded similar results for change in SBP −7.35 mmHg (−8.95 to −5.75; P  < 0.00001), DBP MD −3.29 mmHg (95% CI −5.12 to −1.46; P  = 0.0004) and MAP MD −4.63 mmHg (95% CI −6.18 to −3.09: P  < 0.00001). Sub-analysis revealed that neither clinical, medication, nor demographic participant characteristics, or exercise program features, modified the IRT treatment effect. Conclusion: This individual patient analysis confirms a clinically meaningful and statistically significant effect of IRT on resting SBP, DBP and mean arterial blood pressure.